Kinerja Keuangan Sekolah Swasta Tingkat SMA/SMK/MA Kabupaten Karanganyar Dipengaruhi Akuntabilitas, Transparansi, dan PSAK No 45 - Yasinta Ratna Ambarsari; Erna Chotidjah Suhatmi; Novemi Triyandari Nugroho (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study was to determine the effect of Accountability, Transparency, and PSAK No. 45 on the Financial Performance of Private Schools in their financial reporting. The objects of this research are the principles of accountability, the principles of transparency, PSAK NO 45, and the financial performance of private schools at SMA/SMK/MA level in Karanganyar Regency. Primary data is data used with quantitative and qualitative data types collected through interviews, questionnaires, observation, and documentation. The results of this study explain that partially the variables of Accountability, Transparency, PSAK No. 45 have an influence on the Financial Performance of Schools in Private Schools at the SMA/SMK/MA level in Karanganyar Regency. Simultaneously the variables Accountability, Transparency, PSAK No. 45 have an influence on the Financial Performance of Schools in Private Schools at the SMA/SMK/MA level in Karanganyar Regency.